NEW ANOMALOCARIDID APPENDAGES FROM THE BURGESS SHALE, CANADA - Daley, A; Budd, G (2010)
Abstract: The complex history of description of the anomalocaridids has partly been caused by the fragmentary nature of these fossils. Frontal appendages and mouth parts are more readily preserved than whole-body assemblages, so the earliest work on these animals examined these structures in isolation. After several decades of research, these disarticulated elements were assembled together to reconstruct the anomalocaridid body plan, and a total of three Burgess Shale genera, Anomalocaris, Laggania and Hurdia, were described in full. Here we present new frontal appendage material of additional anomalocaridid taxa from the 'Middle' Cambrian (Series 3) Burgess Shale Formation in Canada, showing that the diversity of anomalocaridids in this locality is even higher than previously thought. Material includes Amplectobelua stephenensis sp. nov., the first known occurrence of this genus outside of China; Caryosyntrips serratus gen. et sp. nov., which is similar to the Anomalocaris appendage but has a straighter outline and a different arrangement of spines; and an appendage that may be either the Laggania appendage or a third morph of the Hurdia appendage. The new anomalocaridid material is contemporaneous with the previously described taxa Anomalocaris, Laggania, and Hurdia, and the differences in morphology between the frontal appendages may reflect different feeding strategies. The stratigraphically lowest locality, S7 on Mount Stephen, yields material from all anomalocaridid taxa, but the assemblages in the younger quarries on Fossil Ridge are dominated by Anomalocaris and Hurdia only. © The Palaeontological Association.